Assessment of radiological vertebral fractures in HIV‐infected patients: clinical implications and predictive factors. Issue 9 (6th May 2015) - Gazzola, L; Savoldi, A; Bai, F; Magenta, A; Dziubak, M; Pietrogrande, L; Tagliabue, L; Del Sole, A; Bini, T; Marchetti, G; d'Arminio Monforte, A
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to evaluate the clinical impact of including lateral spine X‐ray in the screening of bone diseases in HIV‐positive patients. Methods A total of 194 HIV‐positive patients underwent dual‐energy X‐ray absorptiometry (DEXA), lateral spine X‐ray and bone biochemical analysis. Vertebral fractures were identified using a morphometric analysis of X‐rays and classified using the semiquantitative scoring system of Genant et al. For each patient, a spine deformity index (SDI) score was calculated by summing the grades of vertebral deformities. Reductions in vertebral body height of > 25% were considered vertebral fractures, and those < 25% were considered vertebral deformities. Risk factors associated with vertebral fractures were evaluated by univariate and multivariate analysis. Results Vertebral fractures were detected in 24 patients (12.4%) and vertebral deformities in 17 patients (8.7%); 153 patients (78.9%) did not show any vertebral deformity. Among patients with fractures, only two with SDI > 10 reported lumbar pain; the remaining were asymptomatic. Patients over 50 years old showed a higher prevalence of vertebral fracture [24.4% versus 11.8% in patients 41–50 years old (P = 0.05) and 1.9% in patients ≤ 40 years old (P = 0.04)]. No significant increase in the prevalence according to bone mineral density (BMD) reduction was observed, and 70% of fractures were diagnosed in nonosteoporotic patients. Older age [adjusted odds ratio 1.09; 95% confidence interval (CI) 1.03–1.13; P = 0.001] and steroid use (adjusted odds ratio 3.64; 95% CI 1.29–10.3; P = 0.01) were independently associated with vertebral fracture; no association was found with HIV‐ or highly active antiretroviral therapy (HAART)‐related variables. Conclusions A prevalence of vertebral fractures of 12.4% was observed in our HIV‐positive cohort. Given that two‐thirds of fractures occurred in nonosteoporotic patients, spine X‐ray may be considered in patients at increased risk, irrespective of BMD; that is, in elderly patients and/or patients using steroids.